Optimalisasi Pengelolaan Keuangan Sekolah Berkelanjutan Berbasis Maqasid Syariah - Sri Rahayu; Azwansyah Habibie; Sobihatun Nur Abdul Salam; Safrida Safrida; Supriadi Supriadi; Sri Gustina Pane; Neni Sri wahyuni; Jihan Fazira; Inaya Hakim; Dinda Alfira (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
Transparent, accountable, and sustainable school financial management requires adequate financial literacy and competent human resources. However, the partner institution faced several challenges, including limited financial literacy among teachers, conventional and administratively oriented financial management practices, insufficient skills in systematic financial record-keeping, and the limited integration of sustainability principles and maqasid al-Shariah into the management of school financial resources. This community service program aimed to optimize sustainable school financial management based on maqasid al-Shariah by strengthening teachers' financial literacy and competencies. The program involved 14 teachers and employed a participatory and practice-oriented approach comprising needs identification, training, interactive discussions, case studies, basic financial record-keeping practice, mentoring, and evaluation. Changes in participants' understanding were assessed using pre-test and post-test measures, while observations and participant feedback were used to identify changes in skills and attitudes throughout the mentoring process. The results showed an increase in the participants' average score from 56.43 on the pre-test to 82.36 on the post-test, representing an improvement of 25.93 points. Beyond improved understanding, participants demonstrated greater ability to organize financial records systematically and developed a stronger awareness of transparency, accountability, efficiency, and sustainability in school financial management. The integration of maqasid al-Shariah, particularly hifz al-mal, also strengthened participants' awareness of trustworthiness and responsibility in safeguarding and utilizing financial resources. The program enhanced teachers' capacities and established a foundation for more systematic, responsible, and sustainability-oriented school financial management. Periodic mentoring and monitoring are required to maintain the consistent implementation of the program outcomes.